Enhanced Methyl Orange Removal Using a Newly Isolated Bacterial Strain and Potassium‐Iodide‐Doped Hydroxyapatite Nanoparticles. Issue 7 (21st May 2019) - Kilany, Mona; Ibrahim, Essam H.; Alshehri, Ali; Ghramh, Hamed A.
Abstract : Due to the toxicity and mutagenicity of methyl orange (MO), it is necessary to eliminate MO from wastewater. A bacterial strain is isolated and identified that possesses a high MO decolorization ability. Furthermore, the cultural requirements and the decolorization behavior of the bacterial isolate are investigated. Potassium‐iodide‐doped hydroxyapatite (KI‐doped HAp) nanoparticles are synthesized and characterized. The enhancement of the decolorization rate using KI‐doped HAp nanoparticles is experimentally confirmed. The microbial toxicity assessment is evaluated against Bacillus subtilis, and the bacterial isolate is identified as the Enterococcus faecalis strain Kilany MO under accession number KY780590. This strain shows maximum decolorization of MO (86.4%) at 400 mg L −1, pH 6, and 30 °C for 48 h under static conditions. In addition, being extremely tolerant of concentrations of MO of up to 1000 mg L −1 or more, E. faecalis exhibited decolorizing activity through biosorption rather than adsorption. Scanning electron microscopy and energy dispersive X‐ray spectra revealed that KI‐doped HAp nanoparticles are nanorods that are 50–100 nm in size with a Ca/P molar ratio of 1.833. KI‐doped HAp nanoparticles enhanced decolorization, yielding a maximum removal of 95% within 48 h. A microbial toxicity study revealed that the bacterial metabolites are less toxic than MO. Hence, the potential of E. faecalis to withstand high concentrations of MO, especially in the presence of nanoparticles, may start a new trend in wastewater bioremediation strategy. Abstract : A promising, eco‐friendly, cost effective, and functional technique for decoloration of methyl orange (MO) by Enterococcus faecalis strain Kilany MO is demonstrated through biosorption on live cells and adsorption on dead cells. Moreover, the immobilization of cell‐free extract with potassium‐iodide‐doped hydroxyapatite nanoparticles plays an important role in rapid decoloration.